Delivery of the Bioactive Component Paeonol by Dual pH‐Responsive Nanoparticles Enhances Anti‐Metastatic Tumor Efficiency. Issue 1 (4th November 2020) - Liu, Haiting; Li, Jian; Shang, Yinghui; Zhao, Qiangqiang; Wu, Bin; Huang, Xueyuan; Dong, Hang; Gui, Rong; Huang, Rong
Abstract: In spite of several treatments involving chemotherapy, immunotherapy, and molecularly targeted agents, patients with metastatic breast cancers (MBCs) usually have a poor prognosis due to the toxic side effects, poor selectivity, and drug resistance of these treatments. Thus, new effective treatments with reduced side effects are needed. Paeonol (Pae), a bioactive phenol, has anti‐tumor activity, but hydrophobicity, poor bioavailability, and instability limit its anti‐tumor effect. To overcome these problems, we constructed a nanoplatform of calcium phosphate (CA‐P) modified with polyacrylic acid (PAA) and loaded with Pae (Pae@CA‐P/PAA NPs). Pae@CA‐P/PAA NPs possess high drug‐loading levels and dual pH‐responsive properties. Because of the weak acidity of the tumor microenvironment (TME), the platform can passively target tumor sites. Compared with free Pae, Pae@CA‐P/PAA NPs effectively inhibited tumor cell growth and metastasis in vitro and in vivo. In conclusion, the nanoplatform is a promising strategy for the therapy of MBCs. Abstract : A simple strategy was used to fabricate a dual pH‐responsive nanoplatform of calcium phosphate modified with polyacrylic acid and loaded with Paeonol (Pae@CA‐P/PAA NPs) for breast tumor treatment.